Psychometric properties of the Autism Spectrum Disorder in Adults Screening Questionnaire (ASDASQ) in a sample of Italian psychiatric outpatients. (October 2020) - Fusar-Poli, Laura; Bisso, Emanuele; Concas, Ilaria; Surace, Teresa; Tinacci, Silvia; Vanella, Antonio; Furnari, Rosaria; Signorelli, Maria Salvina; Nylander, Lena; Aguglia, Eugenio
Highlights: Autism spectrum disorder (ASD) may remain undiagnosed until adulthood. Screening tool currently available are not always reliable in clinical settings. The ASDASQ is a 10-item tool completed by the clinician. The ASDASQ has shown excellent psychometric properties in the psychiatric population. The ASDASQ could be used as a quick screening tool in different clinical settings. Abstract: Background: The present study aimed to examine the reliability and validity of the Italian version of the Autism Spectrum Disorder in Adults Screening Questionnaire (ASDASQ), a screening tool for autism spectrum disorder (ASD) among psychiatric outpatients. Methods: We recruited 340 subjects via an outpatient psychiatric service in Italy. Forty-eight had a diagnosis of ASD, confirmed after a comprehensive clinical assessment and the administration of the Autism Diagnostic Observation Schedule-2 (ADOS-2). The remaining 292 participants had other diagnoses, confirmed after a careful psychiatric evaluation and the administration of the Structured Clinical Interview for DSM-5 (SCID-5). The ASDASQ was administered to contact clinicians of each subject. Results: The ASDASQ showed outstanding accuracy (AUC = 0.96) in discriminating between ASD and non-ASD patients, with good sensitivity (0.85) and specificity (0.92). Agreement with clinical diagnosis was substantial (k = 0.68). Internal consistency of the tool was good (Cronbach's alpha = 0.82), while intra- (ICC = 0.97) and inter-rater reliability (ICC = 0.92) were excellent. We found also a moderate correlation between ASDASQ and ADOS-2 scores in the ASD sample (r = 0.56). Conclusion: Our findings suggest that the ASDASQ, in the Italian adaptation, may be considered a quick, simple, and effective tool to screen for ASD among psychiatric outpatients. Further studies are needed to evaluate its utility in other clinical settings.